Phytosynthesis of biohybrid nano-silver anchors enhanced size dependent photocatalytic, antibacterial, anticancer properties and cytocompatibility. (February 2021) - Priyadarshini, S.; Sonsudin, Faridah; Mainal, Azizah; Yahya, Rosiyah; Gopinath, V.; Vadivelu, Jamuna; Alarjani, Khaloud Mohammed; Al Farraj, Dunia A.; Yehia, Hany Mohamed
Graphical abstract: Highlights: Phytosynthesis of nano-silver/silver chloride particles (NAg/AgClPs) were achieved. NAg/AgClPs display antibacterial, anticancer activity and low toxicity to normal cells. Mode of nanoparticles antibacterial and mammalian cell toxicity was studied. NAg/AgClPs demonstrated size dependent photocatalytic reduction of methylene blue. Abstract: Metallic silver tactically attains reductant from biomaterials during biosynthesis, though it is still challenging to fasten the rate of stable nano-silver/silver chloride particles (NAg/AgClPs) synthesis. In this study, two different sizes of NAg/AgClPs (15.9 and 24.2 nm) were synthesised using Cissus quadrangularis stem (CQS) extract under microwave irradiation. The synthesised NAg/AgClPs were characterised using high throughput traditional methods. The antibacterial study of these materials demonstrated excellent activity against human nosocomial pathogens. The metabolic activity and viability assay provided strong evidence that the 15.9 nm NAg/AgClPs inhibited the bacterial pathogens better than the 24.2 nm NAg/AgClPs. The cytotoxicity of the as-synthesised NAg/AgClPs was studied towards human A549 adenocarcinomic alveolar basal epithelial cell line and RAW 264.7 macrophage cells. Anticancer activity of both 15.9 nm NAg/AgClPs and 24.2 nm NAg/AgClPs displayed the IC50 values at 85 μg/mL and 90 μg/mL against A549 cells while RAW 264.7 macrophage cells expressed the IC50 values at 130 μg/mL and 140 μg/mL respectively. Further, the synthesised NAg/AgClPs demonstrated high photocatalytic activity towards degradation of environmental pollutant methylene blue (MB) under visible light illumination. Our results suggested that the synthesised NAg/AgClPs can be used to develop novel antimicrobial, anticancer formulations and environmental catalyst.